2021
DOI: 10.1590/1980-549720210018
|View full text |Cite
|
Sign up to set email alerts
|

Who are the people with Alzheimer's disease in Brazil? Findings from the Brazilian Longitudinal Study of Aging

Abstract: Objective: To describe the socioeconomic, behavioral, clinical, and health-related characteristics of Brazilian older adults with Alzheimer's disease (AD). Methods: Baseline data from the Brazilian Longitudinal Study of Aging were analyzed. This nationwide survey interviewed 9,412 adults aged at least 50 years. Self-reported medical diagnosis of AD and exposure variables (sociodemographic, clinical, behavioral, and health-related) were assessed by face-to-face questionnaire-based interview. Multivariate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
19

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 29 publications
0
14
0
19
Order By: Relevance
“…People with Alzheimer’s disease have a high risk of being hospitalised 48 . Another Brazilian study found that Alzheimer’s disease increases the likelihood of hospitalisation, as well as increasing the days hospitalised and the chance of being diagnosed with another chronic condition such as depression or Parkinson’s disease 49 . People with Alzheimer’s have worse health outcomes and are at greater risk of hospitalisation, readmission, increased hospitalisation days and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…People with Alzheimer’s disease have a high risk of being hospitalised 48 . Another Brazilian study found that Alzheimer’s disease increases the likelihood of hospitalisation, as well as increasing the days hospitalised and the chance of being diagnosed with another chronic condition such as depression or Parkinson’s disease 49 . People with Alzheimer’s have worse health outcomes and are at greater risk of hospitalisation, readmission, increased hospitalisation days and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A Doença de Alzheimer (DA) é caracterizada como um distúrbio neurodegenerativo progressivo, que cursa com atrofia cerebral, demência, disfunção da cognição e declínio mental, sendo que a duração média do surgimento dos primeiros sintomas até o desfecho trágico é cerca de 10 a 20 anos (Zhou & Zhang, 2021;Kolahdouzan & Hamadeh, 2017). A DA é reponsável pela terceira maior causa de distúrbios relacionados a idade e, consequentemente, a morte, sendo que no Brasil a prevalência desses pacientes está concentrada principalmente entre 70 e 79 anos e acima de 80 anos, com destaque para as mulheres (67,9%), casadas e viúvas, com apenas educação elementar, aposentados ou desempregados; os dados mostram que os essa prevalência aumentou cerca de 127% desde 1990 e o aumento do número de pessoas com DA pode estar relacionado com a maior expectativa de vida, de forma que a população esperada acima dos 60 anos para 2050 é 284,2% maior em relação ao observado em 2000, com índice de diagnóstico aumentando em 11% por ano acrescido na idade (Feter et al, 2021).…”
Section: Cafeína E Doença De Alzheimerunclassified
“…Nesse sentido, sabemos que as síndromes demenciais tem um papel importante nesse cenário, mundialmente, a Doença de Alzheimer (DA) é responsável por 50-70% dos casos, seguida pela Doença de Parkinson (DP) (Londzin et al, 2021;Hong et al, 2020), além de outras doenças como a Demência Vascular. No Brasil, dados epidemiológicos recentes também confirmam esse padrão, ocupando o segundo lugar no ranking de prevalência de doenças demenciais, com a DA representando 70% dos casos e a DP responsável pela quarta posição no número de hospitalizações dentre as doenças que afetam o sistema nervoso e as funções cognitivas (Santos et al, 2022;Feter et al, 2021).…”
Section: Introductionunclassified
“…In Brazil, it is estimated that 77% of individuals with dementia have not been adequately diagnosed 7 . However, Feter et al 8 reported that in 2016, Brazil had the second highest age-standardized prevalence of dementia in the world, with AD accounting for about 70% of cases.…”
Section: Introductionmentioning
confidence: 99%